Indeks Sentralitas Masyarakat Pesisir pada Gugus Kepulauan dengan Pusat Layanan Wilayah di Pulau Induk (Studi Kepulauan Arar Kabupaten Sorong Papua Barat Daya) - Marasabessy, Ilham; Basri, La; Badarudin, Mohammad Iksan; Bahalwan, Fahriya (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The diversity of coastal and marine resources on archipelago can have a significant economic impact if effective regional connectivity is established. The Arar archipelago as a hinterland area integrated with centralland, has high dynamics related to the characteristics and interactions of communities in managing and utilizing natural resources. The research aims to determine the centrality index of the Arar Islands community with regional service centers on the main island using quantitative descriptive methods. Determining the hierarchy of regions and service centers was carried out in situ and elaborated on Sorong Regency and City BPS data, considering the number and type of facilities in the Arar region and surrounding areas to determine the hierarchy of regional centrality. Centrality analysis using the guttmen scale. The area that has the highest interaction with the people of the Arar Islands is Aimas District at 12.26, while Manyamuk District is an area with a productive orientation trend with an index of 6.05, even though it has a relatively low centrality index than Sorong Manoi District at 9.89. This happens because the interactions carried out tend to be related to the distribution of goods and services, work and the process of fulfilling daily life, rather than institutional entertainment and social activities. On the other hand, the employment opportunities provided in the Aimas and Mayamuk areas are in adequate condition and able to support the lives of the community. in the Arar Islands.